Predicting Intercultural Leadership Readiness using the Indonesian Cultural Empathy Scale (ICES): Evidence from Student Organizations - Lailatul Badriyah (Yayasan Darussalam Bengkulu, 2026)
This study aims to test the influence of the Indonesian Cultural Empathy Scale (ICES) on Intercultural Leadership Readiness to students who are active in the organization. The background of this research is based on the increasing need for adaptive leadership in a multicultural context, especially in Indonesian higher education environments that have ethnic, religious and cultural diversity. This research uses a quantitative approach with predictive correlational design. The research sample consisted of 110 students who were active in organizations, who were selected using purposive sampling techniques. Data were collected through a Likert scale-based questionnaire and analyzed using SPSS, including reliability tests, normality tests, Pearson correlations, and simple linear regression. The research results show that ICES has high reliability (α = 0.878) and has a positive and significant effect on Intercultural Leadership Readiness (β = 0.759; p < 0.001). The determination coefficient value (R² = 0.576) shows that cultural empathy contributes 57.6% to cross-cultural leadership readiness. These findings confirm that cultural empathy is an important factor in shaping inclusive and adaptive leadership in multicultural environments. This research provides theoretical contributions in the development of leadership models based on local cultural contexts, as well as practical implications for the development of student leadership programs in higher education.